Absensi Regionalisme di Asia Timur dari Perspektif Jepang - Arief, Audrey Diva Azzahra; Kalisang, Rahel Jechire (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2024)
The absence of East Asian regionalism has become a problem along with the increasing political tensions and the competition for military power from the member countries of the region. However, the bright spot for the creation of regionalism is not increasingly emerging and instead Japan, China and Korea choose their respective allies in the uncertainty of this international political contestation. History proves the truth today, that disputing countries will not easily cooperate in the same forum unless assisted by a third party. In this case, ASEAN is a liaison through ASEAN+3 and from Japan's perspective this situation is good. Cooperation between Japan and China, Japan and Korea and a mixture of the three often occurs bilaterally or non-bilaterally through ASEAN. Following the flow of the existing problems, a research question was formulated,